The Influence of Family Interaction, Social Support, and Coping Strategies on Family Resilience After Retirement - Fathiyya Basyaasyah; Tin Herawati (Journal of Child, Family, and Consumer Studies, 2025)
The end of a person's working life presents a new challenge as they enter old age. The issues faced by retirees can affect family resilience. This study aims to analyze the influence of family interaction, social support, and coping strategies on family resilience after retirement. The research used a quantitative approach with a cross-sectional study design and purposive sampling method. The study involved 40 families with husbands who had retired within the past three years, were married, and had children, all residing in Cibinong District, Bogor Regency. The results showed that family interaction, social support, and coping strategies were at a moderate level, while family resilience was at a high level. Correlation tests revealed a significant positive relationship between the wife's age and family interaction, a significant negative relationship between the husband's education and social support, and a significant positive relationship between family interaction and social support. Multiple linear regression analysis showed a significant positive influence of the wife's age on family resilience. The husband's age and education had a significant negative influence on family resilience, while family income had a significant positive influence. Nuclear family support and the self-control dimension had a positive effect on family resilience. Meanwhile, the escape-avoidance and planful problem-solving dimensions had a significant negative effect on family resilience. Therefore, efforts are needed by families to maintain effective communication, enhance social support, and practice good emotional management in post-retirement family life.